PENGARUH UMUR DAN PEKERJAAN IBU BAYI TERHADAP PEMBERIAN ASI EKSKULUSIF PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS BATANG BERUH KECAMATAN SIDIKALANG KABUPATEN DAIRI TAHUN 2017 - Nurcahaya Nainggolan; Marta Imelda Br Sianturi; Hilda Yani Karo Karoi (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2021)
Exclusive breastfeeding or exclusive breastfeeding until the baby is 6 months old is very beneficial because it can protect the baby from various diseases that cause infant death. It also benefits the mother, namely reducing postpartum bleeding. This study aims to determine the effect of mother's age and the effect of mother's occupation on exclusive AS1 administration to infants aged 0-6 months in the Working Area of ​​the Batang Beruh Health Center, Sidikalang District, Dairi Regency in 2017. The type of research is observational analytic using a cross sectional design. The study population was all mothers who had babies aged 0-6 months in the Working Area of ​​the Batang Beruh Community Health Center, Sidikalang District, Dairi Regency, totaling 345 people. The research sample was 100 people. In this study, primary data was required using questionnaires and secondary data through the Batang Beruh Community Health Center report. The data analysis used was univariate analysis with the frequency distribution of the research variables, bivariate with the chi-square test, and multivariate with the logistic regression test. The results showed that there was no effect of the age of the baby's mother on exclusive AS1 administration to infants aged 0-6 months (p = 0.574). There is an effect of work (p = 0.044), on exclusive breastfeeding in infants aged 0-6 months. There is no effect of the age of the baby's mother on exclusive breastfeeding in infants aged 0-6 months. There is an influence of the baby's mother's work on exclusive breastfeeding in infants aged 0-6 months